EVAUATION OF THE ORGANIZATION OF THE SALES FORCE OF THE XL COMPANY SERVICE STATION IN KINDU FROM 2017 TO 2019 - LOMBE MULAMBA (International Journal For Research In Business, Management And Accounting, 2024)
The temes relating to the sales force have already been developed by several authors, each addressing a particular aspect. This research adds to the arsenal through the evaluation of the organization of the sales force of a service station called XL Trading Company operational in Kindu for more than five years. It leads to the results according the which, during the period selected, the sale of petroleum products at the said station generally declined, on the one hand ; and that the organization of its sales force is ineffective, on the other hand.